An Overview of English Language in Indonesian Advertising in Printed Media - Engliana Engliana (Journal of English Language and Culture, 2017)
The aim of this paper is looking on the impact of English as a global language from an angle of how English language is used in local printed advertising media in Jakarta particularly on fliers. Discussion takes place by comparing two different brands in the city: a local brand advertisement and an international/multinational brand advertisement which sells similar product. Linguistic elements such as lexical category (verbs, nouns, etc.) are the focal point of the discussion. It can be said, at the end, that the local brands try to get brand power and position in the market through the usage of English language (as language choice), product name, logo, and even the content message in brochures and menus. Meanwhile it seems that the international brand uses adaptation technique to call for Indonesianisation of their product. Keywords: English as global language, advertisement, linguistic elements